President's Message - Knight, Mary (Operating Room Nurses Association of Canada Journal, 2003)
Sometimes we are fortunate, and opportunities arise that take us down a career path that is rewarding and satisfying. However, making plans and strategic choices will place you in control, and nurture your perioperative nursing career.